Santos Rego, M. A.; Lorenzo Moledo, M. y Miguez Salina, G. (2022). Fondos de conocimiento familiar e intervención educativa. Narcea. - Varela Tembra, Juan José (2024)
Santos Rego et al.'s book "Family Knowledge Funds and Educational Intervention: Understanding the Sociohistorical Circumstances of Students" (2022) compiles research on underserved communities and households with deficient socio-educational conditions. It proposes a model of sensitive and contextualized educational practices using a sociocultural approach. The book explores knowledge funds as resources families accumulate to enhance their well-being, presenting examples of their application in diverse communities. A theoretical and methodological framework highlights the importance of integrating and involving families in education, promoting social justice and interculturality.